Experimental murine non-alcoholic steatohepatitis is associated with behavioural, cognitive, and peripheral neuronal dysfunction - V. A. Prikhodko; D. A. Orlyakhina; V. D. Petrova; V. E. Karev; D. Yu. Ivkin; S. M. Napalkova; S. V. Okovityi (Разработка и регистрация лекарственных средств)
Introduction. Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH), the leading causes of chronic liver disease worldwide, are associated with a wide range of psychoneurological complications and conditions. However, the causal relationship between liver and nervous system disease remains poorly understood, which warrants the development of clinically relevant and valid animal models thereof.Aim. The objective of this work was to characterize the short- and long-term psychoneurological and peripheral neuronal deficits that complicate different stages of NAFLD/NASH in mice.Materials and methods. 68 adult male C57Bl/6 mice were randomized into Control or NASH groups. NASH was induced over 3 (Experiment 1) or 6 (Experiment 2) mo using a combined model including a high-fat diet and low doses of carbon tetrachloride. Control group received standard chow, drinking water, and equivolume normal saline. Animal behaviour was assessed by the Open field (OF), Elevated plus maze (EPM), and Light/dark box (LDB) tests at 1, 2, 3, and 6 mo of NASH induction. Visuospatial memory was assessed by the Spontaneous alternation in the T-maze and Novel object recognition tests at 1, 2, and 3 mo of NASH modelling, and using the Barnes maze at 6 mo of NASH induction. Following 3 mo of NASH induction, needle electroneuromyography (ENMG) was performed on the gastrocnemius and biceps muscles with the electrical stimulation of the sciatic and musculocutaneous nerves, respectively. Liver pathology was confirmed by histomorphology. Statistical analysis was performed using Prism 10.2.3 and R 4.2.3 with RStudio 2024.09.0.Results and discussion. Experimental modelling was associated with poorer overall survival (p < 0.05, p < 0.01) and substantial evidence of liver injury, i.e. cholestatic hepatitis, medio- and macrovesicular steatosis, focal necrosis and fibrosis of varying severity (p < 0.05, p < 0.01). Mice with NASH exhibited markers of elevated anxiety in the OF, EPM, and LDB tests (p < 0.05, p < 0.01), which were mostly specific to the very onset of liver disease (1 mo) as well as its later stages (6 mo). NASH was also associated with a significant decrease in spontaneous alternation at 3 mo (p < 0.01), negative object disrimination at 2 mo (p < 0.05), and poorer memory retention in the Barnes maze (p < 0.05, p < 0.01) compared with Control. ENMG data analysis revealed significantly lower peak M-wave amplitudes (p < 0.01) and threshold currents (p < 0.05) in the gastrocnemius, and increased peak latency in the biceps in the NASH group (p < 0.05).Сonclusion. Experimental alimentary/toxic NASH in male C57Bl/6 mice is associated with increased anxiety-like behaviour, visuospatial memory acquisition and retention impairment, and evidence of axonal and demyelinating peripheral motor neuropathy.